1991
DOI: 10.1161/01.atv.11.4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake comparisons between Framingham and rural and Urban Puriscal, Costa Rica. Associations with lipoproteins, apolipoproteins, and low density lipoprotein particle size.

Abstract: To assess cross-cultural relations between dietary intake and plasma lipoproteins, we randomly selected 222 men and 243 women from the urban and rural areas of Puriscal, Costa Rica; related their dietary composition (assessed by a food-frequency questionnaire), fitness level, and body fat to plasma lipids, apolipoproteins, and low density lipoprotein (LDL) particle size; and compared these data with those from a subsample of 280 adults from the Framingham Offspring Study. Total cholesterol and LDL cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 71 publications
(35 reference statements)
2
42
0
Order By: Relevance
“…In addition to age and gender, effects on LDL particle size and density distribution have been shown for abdominal adiposity (149), estrogen (150), and oral contraceptive use (151). Dietary intervention studies have shown that variation in dietary fat and carbohydrate can strongly influence expression of the small LDL phenotype (152,153), and contribute to variations in LDL particle size distribution that are observed among individuals and population groups (154). It has been demonstrated in offspring genetically predisposed to phenotype B that a very low fat, high carbohydrate diet can induce expression of this phenotype (155,156).…”
Section: Genetic and Environmental Influences On The Small Dense Ldl mentioning
confidence: 99%
“…In addition to age and gender, effects on LDL particle size and density distribution have been shown for abdominal adiposity (149), estrogen (150), and oral contraceptive use (151). Dietary intervention studies have shown that variation in dietary fat and carbohydrate can strongly influence expression of the small LDL phenotype (152,153), and contribute to variations in LDL particle size distribution that are observed among individuals and population groups (154). It has been demonstrated in offspring genetically predisposed to phenotype B that a very low fat, high carbohydrate diet can induce expression of this phenotype (155,156).…”
Section: Genetic and Environmental Influences On The Small Dense Ldl mentioning
confidence: 99%
“…All frequencies were converted to number of times per day. The questionnaire, administered by trained interviewers in the subjects' home, included specific items from the Costa Rican diet (Campos et al, 1991), such as rice, beans, plantains, corn tortillas, white bread, salads, chopped vegetables, meat, eggs, cheese, and sugar-sweetened tropical fruit beverages. Subjects selected only one type of fat that was used most frequently for cooking at home.…”
Section: Data Collectionmentioning
confidence: 99%
“…The performance of the FFQ in Costa Rica has been further validated and found satisfactory 14 . The United States Department of Agriculture food composition tables were used at the Channing Laboratory to estimate total energy and nutrient intakes for each subject as described previously 12,13 . The subjects were asked to select only one type of fat or oil that is most frequently used for home cooking or frying.…”
Section: Dietary Assessmentmentioning
confidence: 99%